LEXICAL AND SOCIAL MEANING ANALYSIS IN BALI LANDMARKS - Heryani (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2022)
Bali as one of the best islands in the world has many tourist destinations which are very famous among local and domestic tourists who visit Bali. Beside it is famous for its beautiful and extraordinary beaches, it is also famous for other tourist destinations which make it becomes the Bali landmarks. Here the researcher chooses three Bali landmarks, they are Bajra Sandhi Monument, Garuda Wisnu Kencana, and Tanah Lot. It is important to know the philosophy of each landmark which is the representation of Balinese people, culture, tradition, religion, and other social aspects so the researcher is interested in analyzing the lexical and social meaning of the three Bali landmarks with ethno linguistics approach. The research questions in the study are: 1) What is the lexical meaning of the three Bali landmarks (Bajra Sandhi Monument, Garuda Wisnu Kencana, and Tanah Lot)?; and 2) What is the social meaning of the three Bali landmarks (Bajra Sandhi Monument, Garuda Wisnu Kencana, and Tanah Lot)? Results show that Bajra Sandhi Monument, Garuda Wisnu Kencana, and Tanah Lot have their own lexical and social meaning correlated to one another and represent Balinese people, culture, tradition, religion, and many more